Performance and Application Analysis of a New Optimization Algorithm - Junlong Zheng; Chaiyan Jettanasen; Pathomthat Chiradeja (My University, 2023)
Our research focused on an optimization algorithm. Our work makes three contributions. First, a new optimization algorithm, the Maritime Search and Rescue Algorithm (MSRA), is creatively proposed. The algorithm not only has better optimization performance, but also has the ability to plan the path to the best site. For other existing intelligent optimization algorithms, it has never been found that they have both of these performances. Second, the mathematical model of the MSRA was established, and the computer program pseudo-code was created. Third, the MSRA was verified by experiments.
Keywords: Optimization algorithm; MSRA; Code (set theory); Program optimization; Robotic Path Planning Algorithms